Progressive Multifocal Leukoencephalopathy in HIV-Infected Children: A Case Report and Literature Review - Peninnah Oberdorfer; Charles H. Washington; Kamornwan Katanyuwong; Podjanee Jittamala (Hindawi Limited, 2009)
We report a case of a perinatally HIV-infected patient aged 9 years, who presented with right-sided hemiplegia. His initial CD4 T-cell was of 0.21% (4 cells/μL) and plasma HIV RNA virus of 185 976 copies/mL (log 5.27). Plasma and CSF samples were subsequently positive for JCV. Twelve days after the initiation of highly active antiretroviral therapy (HAART), the MRI showed progressive white matter lesions with asymmetrical deep and subcortical white matter lesions over the left frontotemporoparietal region and the right frontal lobe. Immune Reconstitution Inflammatory Syndrome (IRIS) was suspected, and the patient was treated with methylprednisolone. His clinical symptoms worsened and despite therapy the patient deteriorated.